The Role of the Tuo Kayu Jao Mosque in Culture and Society in Gunung Talang District, Solok Regency, West Sumatra - Azzahra Iqlima Ridha Ilahi; Indri Riani; Rosmawati Rosmawati; Hendra Saputra (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The Tuo Kayu Jao Mosque, located in Tuo Kayu Jao, Solok Regency, is one of the oldest mosques in Indonesia and holds significant historical, geographical, and cultural value. This study aims to analyze the role of the mosque from a historical-geographical perspective and its contribution to the social, cultural, and economic life of the community. The method used is a qualitative descriptive approach, focusing on literature review and the interpretation of geographical conditions as well as the dynamics of the local community. The research findings indicate that the mosque’s location in a highland area with relatively strategic access in the past played a crucial role in the spread of Islam across West Sumatra. Beyond serving as a place of worship, this mosque functions as a center for religious education, the preservation of Minangkabau traditional values, and the reinforcement of the community’s social identity. Furthermore, the existence of the mosque has contributed to economic impacts through various activities such as local trade, skills training, and the management of congregation-based cooperatives. Thus, the Tuo Kayu Jao Mosque plays a multidimensional role that extends beyond religious functions to serve as a driving force for the sustainable social and economic life of the community.